2020
DOI: 10.1080/13696998.2020.1832099
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of anticoagulants and predictors of treatment among hospitalized patients with atrial fibrillation in the USA

Abstract: Objective: To evaluate utilization of anticoagulants (ACs) and the predictors of treatment of patients with a diagnosis of atrial fibrillation (AF) during a hospital stay in the USA. Methods: Patients (!18 years of age) who had a primary or secondary discharge diagnosis code of AF during a hospitalization (without a diagnosis of venous thromboembolism) were identified from the Premier Hospital database (1 January 2016-30 September 2017). AC treatments were examined during hospitalizations to assign AF patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
4
2
Order By: Relevance
“…The proportion of highrisk patients who did not receive any therapy in our study was slightly higher, around 31%, compared to 21% previously reported in the U.S [12]. Likewise, other studies have shown that overall, between 22% to 25% of AF patients do not receive treatment [7,13]. Contrasted with 48% of high-risk patients (CHA 2 DS 2 -VASc ≥2) receiving anticoagulants in our study, the National Anticoagulation Benchmark Outcomes Report established that from 86% of the patients identified as high-risk, only 55% received warfarin in a 2002 study [12].…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The proportion of highrisk patients who did not receive any therapy in our study was slightly higher, around 31%, compared to 21% previously reported in the U.S [12]. Likewise, other studies have shown that overall, between 22% to 25% of AF patients do not receive treatment [7,13]. Contrasted with 48% of high-risk patients (CHA 2 DS 2 -VASc ≥2) receiving anticoagulants in our study, the National Anticoagulation Benchmark Outcomes Report established that from 86% of the patients identified as high-risk, only 55% received warfarin in a 2002 study [12].…”
Section: Discussioncontrasting
confidence: 73%
“…As the patients with undertreated AF are at higher risk of a stroke, our study by default recruited a higher proportion of undertreated patients than what we would have had in a population study. Nevertheless, compared to previous reports in the United States (U.S.), the population demographics and comorbidities are similar despite our predominantly rural population [7,13]. Contrasted to our study, Aronis et al combined data from the GHS, the University of Alabama, and the Boston Medical Center [7].…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…On the other hand, such patients are usually not treated properly with anticoagulation, and are therefore also at high risk for thromboembolic events in clinical practice. Deitelzweig et al reported that prior baseline bleeding was a strong predictor of not receiving any anticoagulation therapy [25]. For patients with a contraindication to OAC who were on oral anticoagulants, use of OAC could signi cantly decrease the incidence of mortality, stroke and all-cause hospitalization during long-term follow-up, compared with those not receiving anticoagulation [24].…”
Section: Discussionmentioning
confidence: 99%